Japanese Idiom Learning through Cognitive Linguistics Concept (Idioms Presentation) - Dedi Sutedi; Juju Juangsih; Linna Meilia Rasiban (Journal of Japanese Language Education and Linguistics, 2024)
Idioms in Japanese are crucial and intricate for pupils to acquire, as they necessitate rote memorization. Occasionally, the figurative interpretation of an idiom involving a Japanese language cannot be inferred from its literal definition. Consequently, pupils must commit them to memory without relying on any mnemonic devices. An effective approach to consider is the application of the principles utilized in cognitive linguistics. Specifically, this involves elucidating the connection between the literal meaning of words and their figurative meanings by examining three rhetorical devices: metaphor, metonymy, and synecdoche. The purpose of this is to offer further support to Japanese language students in comprehending the significance of each idiom they acquire. This study aims to implement a series of steps to teach 27 idioms in the Japanese language to fourth semester students. The objectives of this research are: (1) to describe the figures of speech present in each idiom used as teaching material; (2) to assess the learning outcomes of Japanese idioms after applying three figures of speech to connect the lexical and idiomatic meanings; and (3) to determine if there is a significant difference between the experimental class, where students were given explanations using the three figures of speech, and the control class, where students studied independently. The data analysis reveals that the connection between the literal meaning and figurative meaning of each idiom can be illustrated through the use of metaphor, metonymy, and synecdoche. Furthermore, the t-test analysis demonstrates a notable disparity between students who were taught idioms by utilizing associated figures of speech, as opposed to those who simply memorized them independently. Essentially, using figures of speech to illustrate connections between ideas is significantly more impactful than doing so without them. Moreover, acquiring idioms through this method is widely regarded as significantly more pleasurable and accessible for pupils to actively participate in.